ChemInform Abstract: Visible‐Light Photocatalytic Reduction of Sulfonium Salts as a Source of Aryl Radicals. Issue 42 (1st October 2013) - Donck, Simon; Baroudi, Abdulkader; Fensterbank, Louis; Goddard, Jean‐Philippe; Ollivier, Cyril
Abstract The photoreduction of triarylsulfonium salts in the presence of activated olefins (II) and (IV) leads to the desired products (III) and (V), respectively.